The overgeneralization of regular verbs in simple past pronunciation by students taking Intensive Intermediate Intensive English I due to the lack of oral reinforcement at the Foreign Language Department of the University of El Salvador during the year 2014 - Benavides Velásquez, Esther Abigail; Mejía Cruz, Juan Francisco; Rivera Hernández, José Gerardo (2024)
In the following graduation work is presented one of the main problems of students when learning a new language: overgeneralization of regular verbs in simple past pronunciation. It is well known that overgeneralization is a common issue that students have to face in their daily academic life and this issue usually has its root in the learning process background. Overgeneralization is the phenomenon when one overextends one rule to cover instances to which that rule does not apply. This phenomenon may appear in different aspects such as semantic, syntactic, morphological, or behavioral. It is a systematic way that children create and unconsciously use, and here appears the greater opposition to the idea of imitation. It is creative. “The phenomenon of overgeneralization itself is not in doubt, nor is the creative nature of the psychological processes that cause it" (Marcus, 1992) There are many theories on language acquisition. For example, the relational frame theory (Hayes, et al, 2001), which is selectionist. It is based on Skinners behaviorist approach in which he claims that language acquisition is determined by the type and period of linguistic interaction. The psychological events that the child experiences are a crucial and have great influence in his language acquisition; these include feelings, thoughts and behaviors. The Imitation Theory says that children learn language by imitating the speech of the people around them. It consists of memorizing words and sentences and drawing conclusions from them as to what are the grammatical rules of the language. This theory is probably at least partly correct. There are some things (like the meaning of words) which the child learns by imitation, but there are some things that the theory fails to account for. For instance, children‟s speech is full of errors. In individual cases this is due to the fact that language is complex and a child‟s first attempt is often not successful. It is commonly believed that children acquire their mother tongue through imitation of parents, caregivers, or people in their environment. Furthermore, some approaches were neutral in that they considered the environment and biological influences. For example, the Emergentist theories, such as MacWhinney's (2005)